Clinical significance of the abnormal Doppler spectrum of renal blood flow in patients with long-term transplant dysfunction - V. V. Yakymenko (Zaporožskij Medicinskij Žurnal)
Relevance. One of the main causes of graft loss in a recipient after kidney transplantation is acute rejection.